E. I. SHWARTZ: AT THE ORIGINS OF MOLECULAR MEDICINE - S. N. Pchelina (Учёные записки Санкт-Петербургского государственного медицинского университета им. Акад. И.П. Павлова, 2020)
Eugene I. Schwartz (1940–2003), the first head of the Department of Molecular Genetic Technologies of the Research Center of the Pavlov University, a well-known geneticist, stood at the origins of molecular medicine in Russia. The results of the research work of E. I. Schwartz are introduced now in the work of many clinical centers. He also created one of the first course of medical genetics for physicians in our country. This article reflects the main milestones of the scientific and pedagogical way of E. I. Schwartz, and discusses the achievements of his teams.